The Influence of Pedagogic, Profesional Competency, and Work Motivation on Improving Teacher Performance of Junior High School in Tegal Regency - Dewi Pangestuti; -, Fajar Rasyid; Maufur; Basukiyatno (Cakrawala: Jurnal Pendidikan, 2024)
This study used quantitative approach with data collection technique using aquestionnaire. The puirpose of the study is to analyze the influence of pedagogicalcompetence, professional competence and work motivation on improving theperformance of English teachers with the status of Civil Servants of State Junior HighSchools who have been certified educators throughout Tegal Regency partially andsimultaneously. Data analysis used descriptive linear regression analysis to test R squareand hypothesis testing partially and simultaneously with the t test and F test. The resultsof the study using the t test (partial) proved that pedagogical competence, professionalcompetence and work motivation each had a positive and significant effect on improvingteacher performance.